A Brighton Collaboration standardized template with key considerations for a benefit/risk assessment for an inactivated viral vaccine against Chikungunya virus. Issue 35 (19th August 2022) - Hernandez, Libia Milena; Sumathy, K.; Sahastrabuddhe, Sushant; Excler, Jean-Louis; Kochhar, Sonali; Smith, Emily R.; Gurwith, Marc; Chen, Robert T.; ,
Abstract: Inactivated viral vaccines have long been used in humans for diseases of global health threat (e.g., poliomyelitis and pandemic and seasonal influenza) and the technology of inactivation has more recently been used for emerging diseases such as West Nile, Chikungunya, Ross River, SARS and especially for COVID-19. The Brighton Collaboration Benefit-Risk Assessment of VAccines by TechnolOgy (BRAVATO) Working Group has prepared standardized templates to describe the key considerations for the benefit and risk of several vaccine platform technologies, including inactivated viral vaccines. This paper uses the BRAVATO inactivated virus vaccine template to review the features of an inactivated whole chikungunya virus (CHIKV) vaccine that has been evaluated in several preclinical studies and clinical trials. The inactivated whole CHIKV vaccine was cultured on Vero cells and inactivated by ß-propiolactone. This provides an effective, flexible system for high-yield manufacturing. The inactivated whole CHIKV vaccine has favorable thermostability profiles, compatible with vaccine supply chains. Safety data are compiled in the current inactivated whole CHIKV vaccine safety database with unblinded data from the ongoing studies: 850 participants from phase II study (parts A and B) outside of India, and 600 participants from ongoing phase II study in India, and completed phase I clinical studies for 60 subjects. Overall, the inactivated whole CHIKV vaccine has been well tolerated, with no significant safety issues identified. Evaluation of the inactivated whole CHIKV vaccine is continuing, with 1410 participants vaccinated as of 20 April 2022. Extensive evaluation of immunogenicity in humans shows strong, durable humoral immune responses.